Dabigatran Acylglucuronide, the Major Metabolite of Dabigatran, Shows a Weaker Anticoagulant Effect than Dabigatran - Jong-Min Kim; Jihyeon Noh; Jin-Woo Park; Hyewon Chung; Kyoung-Ah Kim; Seung Bin Park; Jun-Seok Lee; Ji-Young Park (MDPI AG, 2022)
Dabigatran (DAB) is an orally administered thrombin inhibitor. Both DAB and its main metabolite dabigatran acylglucuronide (DABG) have established anticoagulant effects. Here, we aimed to compare the relative anticoagulant effects of DABG and DAB in humans. Anticoagulant effects of DAB and DABG were measured in vitro using a thrombin generation assay. Additionally, their effects on other coagulation assays including PT, aPTT, TT, and fibrinogen were compared. Both DAB and DABG showed inhibitory effects on thrombin generation in a dose-dependent manner, but DABG exhibited a weaker inhibitory effect than that of DAB. The IC50 values of DAB and DABG on thrombin generation AUC were 134.1 ng/mL and 281.9 ng/mL, respectively. DABG also exhibited weaker anticoagulant effects than DAB on PT, aPTT, and TT. The results of the present study indicate that the anticoagulant effect of DABG, a main active DAB metabolite, is weaker than that of DAB.